Plants, People and Places : Recent Studies in Phytolithic Analysis. - Madella, Marco (Oxbow Books, 2007)
Phytoliths - rigid microscopic bodies that occur in most plant species - have gone a long way since that day when Darwin became curious about a fine powder deposited on the instruments of the HMS Beagle. This fascinating subject started because of curiosity, and in that respect it was a good start since curiosity is probably the most important drive behind first-rate research. Fortunately curiosity is still present in phytolith research; the articles in this book are full of curiosity and ingenuity. Phytolith research has grown since the times of Darwin and in the last three decades has bloome.